2016
DOI: 10.1177/1526602816655521
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholinesterase Levels Are Associated With 2-Year Ischemic Outcomes After Angioplasty and Stenting for Peripheral Artery Disease

Abstract: Low CHE is associated with an increased risk of long-term adverse ischemic events following SFA angioplasty with stent implantation for PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
“…Exclusion criteria were a known aspirin or clopidogrel intolerance (allergic reactions, gastrointestinal bleeding), a therapy with vitamin K antagonists (warfarin, phenprocoumon, acenocoumarol) or direct oral anticoagulants (dabigatran, rivaroxaban, apixaban, edoxaban), a treatment with ticlopidine, dipyridamole or nonsteroidal anti-inflammatory drugs, a family or personal history of bleeding disorders, malignant paraproteinemias, myeloproliferative disorders or heparin-induced thrombocytopenia, severe hepatic failure, acute and chronic inflammatory diseases, known qualitative defects in thrombocyte function, a major surgical procedure within one week before enrolment, a platelet count <100,000 or >450,000/µL and a hematocrit <30% as previously described [27,28].…”
Section: Study Populationmentioning
confidence: 99%
“…Clinical follow-up was assessed at regular visits of the study participants to the outpatient department of the Division of Vascular Medicine at the Medical University of Vienna and via telephone calls, respectively. As in previous studies [27,28], the primary endpoint was defined as the composite of the first occurrence of any of the following events: nonfatal myocardial infarction (MI), nonfatal stroke or transient ischemic attack (TIA), cardiovascular death, and sonographically confirmed >80% target vessel restenosis or reocclusion within 2 years after peripheral angioplasty and stenting.…”
Section: Clinical Endpointsmentioning
confidence: 99%
“…Besides established cardiovascular risk factors, easy-accessible laboratory parameters may be of use to optimize risk stratification in PAD. Indeed, several markers have been associated with the occurrence of ischemic outcomes after endovascular interventions for PAD [ 4 , 5 , 6 ]. For instance, low levels of serum cholinesterase and high levels of α-hydroxybutyrate dehydrogenase were linked to an increased risk of TVR and atherothrombotic outcomes, respectively [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several markers have been associated with the occurrence of ischemic outcomes after endovascular interventions for PAD [ 4 , 5 , 6 ]. For instance, low levels of serum cholinesterase and high levels of α-hydroxybutyrate dehydrogenase were linked to an increased risk of TVR and atherothrombotic outcomes, respectively [ 5 , 6 ]. Moreover, recent studies reported that platelet-to-lymphocyte (PLR), neutrophil-to-lymphocyte (NLR) and lymphocyte-to-monocyte (LMR) ratios were able to predict the occurrence of critical limb ischemia in PAD [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%